2021
DOI: 10.3390/ijms22084183
|View full text |Cite
|
Sign up to set email alerts
|

Atypical p38 Signaling, Activation, and Implications for Disease

Abstract: The mitogen-activated protein kinase (MAPK) p38 is an essential family of kinases, regulating responses to environmental stress and inflammation. There is an ever-increasing plethora of physiological and pathophysiological conditions attributed to p38 activity, ranging from cell division and embryonic development to the control of a multitude of diseases including retinal, cardiovascular, and neurodegenerative diseases, diabetes, and cancer. Despite the decades of intense investigation, a viable therapeutic ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 211 publications
0
43
0
Order By: Relevance
“…Considering that inflammatory response is usually triggered by mitogen‐activated protein kinase (MAPK) signaling, such as p38 and Jun‐NH(2)‐terminal kinase (JNK), p65 nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF‐κB) signaling, and Janus kinase (JAK)‐signal transducer and activator of transcription 1/3(STAT1/3) signaling, 22 , 23 , 24 , 25 , 26 we further explored whether Mettl3 promoting oxLDL‐induced inflammatory response in macrophages is associated with these signaling pathways. As shown in Figure 3A , oxLDL stimulation significantly increased the protein expressions of phosphorylated p38 (p‐p38), p‐JNK1/2, p‐p65, p‐STAT1, and p‐STAT3, while Mettl3 knockdown obviously suppressed the upregulation of total STAT1 and p‐STAT1 protein expressions.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that inflammatory response is usually triggered by mitogen‐activated protein kinase (MAPK) signaling, such as p38 and Jun‐NH(2)‐terminal kinase (JNK), p65 nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF‐κB) signaling, and Janus kinase (JAK)‐signal transducer and activator of transcription 1/3(STAT1/3) signaling, 22 , 23 , 24 , 25 , 26 we further explored whether Mettl3 promoting oxLDL‐induced inflammatory response in macrophages is associated with these signaling pathways. As shown in Figure 3A , oxLDL stimulation significantly increased the protein expressions of phosphorylated p38 (p‐p38), p‐JNK1/2, p‐p65, p‐STAT1, and p‐STAT3, while Mettl3 knockdown obviously suppressed the upregulation of total STAT1 and p‐STAT1 protein expressions.…”
Section: Resultsmentioning
confidence: 99%
“…JNK and p38 are well-studied signaling cascades that are essential for vital cellular activities [4,5]. The activation of MAPK JNK and p38 are mediated by several members of the evolutionary conserved upstream mitogen-activated protein kinases kinase (MAP2K) family [6][7][8]. Such diversity in the repertoire of upstream activators might, in turn, define the specificity of the stimuli-induced pathway activation.…”
Section: Introductionmentioning
confidence: 99%
“…The downstream pathway of RhoA diverges into p38 MAPK and Rho-associated kinase (ROCK) signaling. Aside from a plethora of reports concerning the proinflammatory effect of p38 MAPK (90)(91)(92), it has also been reported that sustained p38 MAPK is vital for cell survival under genotoxic stress (13,93,94). In parallel, ROCK signaling manipulates the stress fiber formation and cellular contractility (95).…”
Section: Genotoxicity and Cancer Developmentmentioning
confidence: 99%